WARAK NGENDOG SEBAGAI INSPIRASI DALAM KARYA SENI LUKIS BATIK - NOFITA, AELIYA (Universitas Negeri Semarang, 2017)
One of the traditional art assets that is owned by Semarang City is the presence of visual culture (art) Warak Ngendog, which is a work of art that became the main mascot in Dugderan ritual tradition. In this project study, Warak Ngendog is not presented in the form of three-dimensional statue but in the form of two-dimensional batik painting. Hopefully by using batik technique in painting making, it will be able to preserve and develop batik making technique in Indonesia. The purpose of this project is to produce batik painting with Warak Ngendog as a source of inspiration. The methods used include the selection of tools and materials, work techniques and the process of work. Based on batik tulis technique that is adopted as the making technique, the media used are materials (cloth berkolin, candle wax, paraffin wax, indigosol color paint, naphthol and salt color paint, koppel soga paint color), tools (canting, brush, electric batik stove and wok, watercolor pencil, cotton bud), equipment (sketch paper, pencil and eraser, gawangan, chair, spanram, plastic cup, cloth, apron, big bucket, pot, big drum, stove) and batik tulis making technique. The process of work is divided into two steps: conceptualization stage and visualization stage. The process of creation is through the stages of data searching, reference searching for batik techniques, preparing tools and materials, making designs, moving the design into cloth (molani), nyanting stage 1 (ngengreng), nembok, stage 1 (colet), nyanting stage 2 (ngisen -isen), coloring stage 2 (dye), nyanting stage 3, coloring stage 3 (dye), nyanting stage 4, coloring stage 4 (dye), nglorot, packaging. The author produces twelve batik painting artworks with Warak Ngendog figure in size 45cm x 45cm, 45cm x 90cm and 60cm x 60cm. Media exploration is done to get more interesting color effects, including the use of sungging technique, fractional technique and color splash technique. This project is expected to inspire UNNES academics in painting field especially art students.